Medication Recommendation, Counseling, and Pricing for Nasal Sprays in German Community Pharmacies: A Simulated Patient Investigation - Bernhard Langer; Christian Kunow; Tim Dethloff; Sarah George (Advances in Respiratory Medicine, 2025)
For the self-medication of nasal congestion following a common cold, decongestant nasal sprays can be recommended according to the medicine guidelines. In Germany, these are only available in community pharmacies (CPs) with free pricing. The aim was to analyze the medication recommendation, counseling, and pricing. A covert simulated patient study, internationally recognized as the “gold standard”, was conducted in all CPs of two medium-sized cities in north-eastern Germany. Each CP was visited twice (86 visits) with the identical scenario by one female and one male simulated patient. At the beginning, they asked for a nasal spray and, when asked, stated that they had had nasal congestion for three days. Slightly more than half (54.7%, 47/86) of the recommended nasal sprays were free of preservatives. The median counseling score was 2.0 out of 8 points, with a significantly higher score observed for the female SP (p = 0.004). Information on the maximum intake duration of five days recommended in the German pharmacy guideline was not provided during any visits. The prices varied in total from EUR 1.95 to EUR 6.22. Therefore, measures by the legislator and the chambers of pharmacists are necessary to sustainably improve the medication recommendation, the counseling, and the price transparency.